2022
DOI: 10.3390/nu14235081
|View full text |Cite
|
Sign up to set email alerts
|

Milk Exosomal miR-27b Worsen Endoplasmic Reticulum Stress Mediated Colorectal Cancer Cell Death

Abstract: The relationship between dietary constituents and the onset and prevention of colorectal cancer (CRC) is constantly growing. Recently, the antineoplastic profiles of milk and whey from Mediterranean buffalo (Bubalus bubalis) have been brought to attention. However, to date, compared to cow milk, the potential health benefits of buffalo milk exosome-miRNA are still little explored. In the present study, we profiled the exosomal miRNA from buffalo milk and investigated the possible anticancer effects in CRC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 71 publications
0
25
0
1
Order By: Relevance
“…118 Gao et al (2021) also found that yak milk exosomes increased the survival of mouse intestinal crypt epithelial cells under hypoxia and confirmed that this was associated with the targeting of the carried miR-34a to inhibit hypoxia-inducible factor HIF-α expression, which in turn promoted intestinal epithelial cell proliferation and differentiation. 119 However, in a recent study by Martino et al (2022), it was found that miR-27b, which is abundant in buffalo milk exosomes, exhibited potent cytotoxicity and induced apoptosis in both Caco-2 cells and HT-29 cells; further studies revealed that overexpression of miR-27b suppressed the expression of PERK/ IRE1/XBP1 and CHOP proteins, further exacerbating the apoptosis rate. 120 In addition, endogenous miRNAs can also regulate intestinal tight junction protein expression at the transcriptional level.…”
Section: Milk-derived Mirnas Regulate Mechanical Barriersmentioning
confidence: 98%
See 2 more Smart Citations
“…118 Gao et al (2021) also found that yak milk exosomes increased the survival of mouse intestinal crypt epithelial cells under hypoxia and confirmed that this was associated with the targeting of the carried miR-34a to inhibit hypoxia-inducible factor HIF-α expression, which in turn promoted intestinal epithelial cell proliferation and differentiation. 119 However, in a recent study by Martino et al (2022), it was found that miR-27b, which is abundant in buffalo milk exosomes, exhibited potent cytotoxicity and induced apoptosis in both Caco-2 cells and HT-29 cells; further studies revealed that overexpression of miR-27b suppressed the expression of PERK/ IRE1/XBP1 and CHOP proteins, further exacerbating the apoptosis rate. 120 In addition, endogenous miRNAs can also regulate intestinal tight junction protein expression at the transcriptional level.…”
Section: Milk-derived Mirnas Regulate Mechanical Barriersmentioning
confidence: 98%
“…119 However, in a recent study by Martino et al (2022), it was found that miR-27b, which is abundant in buffalo milk exosomes, exhibited potent cytotoxicity and induced apoptosis in both Caco-2 cells and HT-29 cells; further studies revealed that overexpression of miR-27b suppressed the expression of PERK/ IRE1/XBP1 and CHOP proteins, further exacerbating the apoptosis rate. 120 In addition, endogenous miRNAs can also regulate intestinal tight junction protein expression at the transcriptional level. For example, miR-29a can target and regulate CLDN1 expression and alleviate the trinitrobenzene sulfonic acidinduced pathological decrease in tight junction protein ZO-1 expression.…”
Section: Milk-derived Mirnas Regulate Mechanical Barriersmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, bovine MDEs exhibited anti-inflammatory effects in murine models of colitis [ 573 , 574 ]. Notably, miR-148a-3p and MDE miR-27b exert tumor suppressive functions in CRC [ 575 , 576 , 577 ].…”
Section: Discussionmentioning
confidence: 99%
“…N. Kumar et al, 2022;D. Li et al, 2022;Louisville, 2011;Martino et al, 2022;Munagala et al, 2016;Raimondo et al, 2015;Tajik et al, 2022;Takakura et al, 2022;H. Tao et al, 2020;Yamauchi et al, 2019;M.…”
Section: Bioticsunclassified